Analisis Pelaksanaan Program PKH dalam Upaya Meningkatkan Kesejahteraan Keluarga di Kota Tanjungpinang, Kepulauan Riau - Maretta Purba, Ave; Kartini Br. Pakpahan, Jelita; Nababan, Rosdiana; Niko, Nikodemus (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Poverty remains a pressing concern globally, and Indonesia is no exception. This study investigates the effectiveness of the Indonesian government's poverty alleviation efforts, focusing on the Conditional Cash Transfer (PKH) program, implemented since 2008. Employing a qualitative, descriptive research approach, data was gathered through interviews and literature studies. The research reveals that PKH assistance, provided in both cash and non-cash forms, has significantly contributed to improving economic, educational, and health aspects of beneficiary households. The disbursement, occurring four times annually through the Prosperous Family Card via Bank Himbara, involves a strategic allocation of Rp. 600,000 per installment. Financial resources and coordination emerge as crucial supporting factors, impacting the program's success. However, individual conflicts pose a challenge to PKH implementation, especially in cases where participants perceive themselves differently in terms of economic status. Understanding these dynamics is essential for optimizing poverty alleviation efforts in Indonesia.